Cytotoxic Effects of Citrus Peels on Breast Tumor: Opportunities for Waste to Raw Material Conversion - Yakinci, Omer Faruk; Emerce, Esra; Gurbuz, Perihan; Demirel, Murside Ayse; Ceribasi, Songul; Suntar, Ipek (Amer Chemical Soc, 2025)
Citrus species have long been known for their rich nutritional value. Recent research has shed light on their therapeutic potential, particularly in cancer treatment. Citrus peels, on the other hand, often discarded as waste, contain a wealth of bioactive compounds, such as flavonoids, coumarins, and essential oil components, which have proven medicinal properties. Converting Citrus peels from waste products to medicinal raw materials is a crucial approach in both healthcare and sustainability. Therefore, the present study aims to investigate the cytotoxic potential of the peels of Citrus aurantium L., Citrus maxima (Burm.) Merr. (syn. Citrus grandis), Citrus medica L. and Citrus paradisi Macfad. cultivated in Turkiye, and to find out the compounds responsible for the cytotoxic activity. The cytotoxic effects of the peel extracts were evaluated on MCF-7 cell lines according to bioactivity-guided fractionation and isolation assay procedures. The compounds CAS-5 (isomeranzin), CAS-10 (3-methoxy nobiletin), CAS-11 (nobiletin), and CAS-12 (tangeretin) were isolated. In silico analyses conducted on the isolated compounds provided supporting information for the results obtained from in vitro experiments regarding their anticancer activity. Indeed, one of the key components of Citrus fruits is polymethoxy flavonoids (PMFs), a group of bioactive constituents recognized for their anti-inflammatory, antioxidant, and anticancer activities. As a valuable byproduct of Citrus waste, PMFs offer a dual benefit by reducing waste while providing a natural source of bioactive compounds and making them an exciting research area in cancer management. The therapeutic promise of PMFs lies not only in their ability to combat cancer but also in their potential to contribute to sustainable practices.
Keywords: Nobiletin; Polymethoxyflavones; Proliferation; Tangeretin; Apoptosis; Toxicity; Growth; Cells